Frozen Conundrum: Unveiling the Ecological Impacts of Snow Pollution Through Diverse Case Studies (London Journal of Research In Science: Natural and Formal, 2024)
This study dives into the usually ignored area of snow pollution, shedding light on the complicated network of biological repercussions caused by impurities in pure frozen environments. Our research, which looks at the origins and types of contaminants found in snow, reveals the complex interplay between industrial emissions, automobile activity, and atmospheric deposition. We investigate the socioeconomic repercussions, including implications for human health and the tourist sector, using a multidisciplinary approach. As snow pollution becomes a growing worldwide problem, our study intends to increase awareness while also encouraging educated decision-making and long-term policies to limit its widespread impacts on vulnerable ecosystems. We demonstrate the critical necessity for proactive environmental policy to protect the purity of snow-covered landscapes via a thorough assessment of case studies and scientific evidence.
Keywords: contaminants; ecosystems; Snow Pollution; Ecological Impacts; Environmental Policies.